Spatial spillover effect of service industry agglomeration on industrial structure upgrading: Evidence from China - Bing, Le Xiao; Aralas, Sarma Binti (Asian Journal of Empirical Research, 2024)
The industrial structure upgrading is a significant indicator in the High-quality economic development. Despite the crucial role that the cluster of service sectors play in improving the industrial system, the research on the impact of service industry agglomeration on industrial structure upgrading is scant, especially the spatial correlation between them. This paper aims to discuss this objective. The current study employs the Spatial Durbin Model to examine the association between service industry gathering and the advancement of industrial systems based on the panel data of Chinese provincial units for the years 2000 to 2020. Findings from the empirical analysis disclose that the concentration of service-related activities in the same province plays a notable role in the optimization of the industrial framework. Moreover, service industry agglomeration demonstrates a noteworthy spatial spillover effect. The gathering of the service industry breaks through geographical constraints and facilitates the enhancement of industrial framework in adjacent regions through radiation effect. Subsequently, the enhancement of the industrial framework in neighboring areas further stimulates the local industrial configuration through spill-over impacts. This research provides a theoretical framework for analyzing the spatial correlation between the service industry group and the enhancement of the industrial framework, and presents practical reference for local authorities to foster the transformation of industrial structure.